The utility of C-reactive protein and procalcitonin for sepsis diagnosis in critically burned patients: A preliminary study. Issue 4 (December 2015) - Egea-Guerrero, Juan J; Martínez-Fernández, Carmen; Rodríguez-Rodríguez, Ana; Bohórquez-López, Angélica; Vilches-Arenas, Angel; Pacheco-Sánchez, María; Guerrero, Juan M; Murillo-Cabezas, Francisco
Objective: To assess the utility of C-reactive protein (CRP) and procalcitonin (PCT) as biomarkers of infection in patients with severe burn injury. Methods: The present study included severe burn injury patients consecutively admitted to the Virgen del Rocío University Hospital (Andalucia, Spain) intensive care unit during a 12-month period. The variables of interest were: age, sex, mechanism of injury, percentage of burned body surface area, the Abbreviated Burn Severity Index (ABSI) and the absence/presence of sepsis. The authors analyzed serum levels of CRP and PCT at admission and every 48 h thereafter until intensive care unit discharge or death. Each determination was considered to be a sample or unit of analysis. Results: A total of 157 determinations were analyzed from 17 severe burn injury patients. Fifty-four samples were considered to be septic, 25 of which corresponded to the first day of a new onset of sepsis. The mean duration of these symptoms was four days (interquartile range two to five days). Significant differences were found in the distributions of CRP and PCT values between sepsis and no-sepsis samples. Analysis of the changes in these biomarkers over time showed that PCT increase (ΔPCT) differentiated these diagnoses, whereas CRP increase (ΔCRP) did not. ROC curve analysis revealed that ΔPCT could predict positive sepsis samples (area under the curve 0.75 [95% CI 0.58 to 0.90]; P=0.003). Conclusion: These preliminary results showed that PCT had a better discriminatory capacity than CRP for identifying infectious processes in patients with severe burn injury. A larger sample size would be needed to confirm these results.